Experimental Evidence on the Impact of Food Advertising on Children’s Knowledge about and Preferences for Healthful Food - Lucia A. Reisch; Wencke Gwozdz; Gianvincenzo Barba; Stefaan De Henauw; Natalia Lascorz; Iris Pigeot (Journal of Obesity)
To understand the rising prevalence of childhood obesity in affluent societies, it is necessary to take into account the growing obesity infrastructure, which over past decades has developed into an obesogenic environment. This study examines the effects of one of the constituent factors of consumer societies and a potential contributory factor to childhood obesity: commercial food communication targeted to children. Specifically, it investigates the impact of TV advertising on children’s food knowledge and food preferences and correlates these findings with their weight status. Evaluations of traditional information- and education-based interventions suggest that they may not sustainably change food patterns. Based on prior consumer research, we propose five hypotheses, which we then test using a subsample from the IDEFICS study, a large-scale pan-European intervention study on childhood obesity. The results indicate that advertising has divergent effects on children’s food knowledge and preferences and that food knowledge is unrelated to food preferences. This finding has important implications for both future research and public policy.